Study of Succession and Role of Family Members in Family Business - Agus Santoso; Susilo Toto Raharjo (Budapest International Research and Critics University, 2022)
The growth of the family business cannot be separated from the problems that occur among fellow family members, such as the crisis of trust of fellow family members, conflicts in decision making, conflicts in leadership succession (successor to the throne), differences in managerial mindset between the first generation (founder) and the second generation (successor). Socio-Emotional Wealth (SEW) is one of the non-financial factors that can affect the sustainability of the family business, both during the transition process and the sustainability of the business. In addition, strong leadership, familial values, organizational transformation, succession, culture and attractive talents are needed to build longevity from generation to generation and the development of the family business. This research focuses more on family business succession, SEW, and family business diversification. The purpose of this study is to test the success of the succession process in business continuity in family companies, as well as to test the role and commitment of family members in business diversification in family companies. This research uses qualitative methods with a case study approach. Techniques in collecting data are observation and in-depth interviews. The results of the study obtained show that the commune and good relationships between family members, as well as the values and family culture maintained by the company will form a good and healthy Socio-Emotional Wealth. Where a healthy SEW will greatly affect the company's decision making during the succession process, diversification, and continuity of the family business.